2000
DOI: 10.1136/thorax.55.6.471
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantitation of circulating neutrophil and eosinophil activation in asthmatic patients

Abstract: Background-Asthma has been associated with eosinophil activation, measured in serum, sputum, bronchoalveolar lavage (BAL) fluid, and urine. A whole blood automated method was developed to assess eosinophil and neutrophil activity in terms of peroxidase content and cell morphology using the Bayer haematology analyser. The method was applied to an in vitro stimulation model when fMLP was added to whole blood and the samples were then analysed for changes in granularity and shape. In addition, cells stimulated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…In a previous study using the H1 analyser (the predescessor to the Advia 120), we have shown that there is evidence of peripheral blood neutrophil activation in patients with asthma [18]. This automated whole blood method requires minimal sample processing, and results are potentially available within minutes of sampling.…”
Section: Introductionmentioning
confidence: 94%
“…In a previous study using the H1 analyser (the predescessor to the Advia 120), we have shown that there is evidence of peripheral blood neutrophil activation in patients with asthma [18]. This automated whole blood method requires minimal sample processing, and results are potentially available within minutes of sampling.…”
Section: Introductionmentioning
confidence: 94%
“…16,17 Many evidences show a correlation between obesity and increased risk of bronchial asthma. Altered GT and IR are believed to play an significant role in asthma, although precise data are not available.…”
Section: Discussionmentioning
confidence: 99%
“…The chemotherapy regimens selected were: doxorubicin þ paclitaxel (ADM-PCX) or epidoxorubicin þ cychlophosphamide þ fluorouracile (FEC) standard dose for breast cancer in 22 cases; cis-diaminedichloroplatinum þ etoposide for nonsmall cell lung cancer in two cases; methotrexate þ vinblastine þ doxorubicin þ cis-diaminedichloroplatinum (M-VAC) for bladder cancer in one case; mitoxantrone þ cychlophosphamide þ vincristine þ prednisone (CNOP) for B-cell lymphoma in two cases; vinblastine þ ifosfamide þ cis-diaminedichloroplatinum (DICE) for testicular cancer in two cases; epidoxorubicin þ cis-diaminedichloroplatinum þ fluorouracile (ECF) for gastric cancer in one case. All chemotherapy regimens had an expected nadir after 7 days from chemotherapy (8).…”
Section: Materials and Methods Patient Characteristicsmentioning
confidence: 99%
“…Bayer hematology analyzer can also measure the myeloperoxidase intracellular index (MPXI). MPXI may raise in patients with unstable angina and acute myocardial infarction, following treatment with granulocyte-colony stimulating factor (G-CSF), and in lymphoma transplant patients who develop bacteremia (8).…”
mentioning
confidence: 99%